Chromatin Accessibility Regulates Gene Expression and Correlates With Tumor-Infiltrating Immune Cells in Gastric Adenocarcinoma - Huang, Chenshen; Huang, Runzhi; Chen, Hong; Ni, Zhizhan; Huang, Qi; Huang, Zongqiang; Ge, Bujun (Frontiers in Oncology, 2021)
Background: Gastric cancer is the third most fatal malignant tumor type worldwide. We explored novel prognostic markers for gastric adenocarcinoma (STAD) using co-analysis of chromatin accessibility (ATAC-seq), mRNA gene expression (RNA-seq), and overall survival. Methods: We used the assay for transposase-accessible chromatin using sequencing (ATAC-seq) profiles of 21 STAD samples from TCGA database and utilized R packages of karyoploteR and ChIPseeker on the ATAC-seq profiles to identify the genes with chromatin accessibilities in their promoter regions. The RNA-seq profiles of 375 STADs and 32 normal solid tissue samples were acquired from TCGA and were processed by edgeR for the differentially expressed genes (DEGs) at the mRNA level. The DEGs with chromatin accessibilities in promoter regions were further filtered using the Pearson correlation with TP53 expression. After co-analysis, the genes were identified for the prognostic value using the Kaplan–Meier method, followed by Pearson correlation analysis with significant pathways. To verify these results, we acquired clinical samples from 30 patients with STAD for qPCR and paraffin sections from 12 patients with STAD for immunohistochemistry (IHC). Multidimensional database validations were also performed to prevent the bias introduced by the use of a single database. Results: We identified 11557 DEGs and 57 genes with chromatin accessibilities. The co-analysis of ATAC-seq, RNA-seq, and clinical survival data revealed that interleukin-18 binding protein (IL18BP), with significant chromatin accessibility in its promoter region and differential expression at the mRNA level, might be directly regulated by TP53 and influence STAD prognosis. Further, gene set variation analysis indicated that IL18BP may impact the survival of patients with STAD in an immune-related manner. According to the CIBERSORT algorithm and Pearson correlation, the integration of IL18BP and CD4+ T memory cells may play an important role in the prognosis of patients with STAD. Conclusion: IL18BP may serve as a novel prognostic marker in STAD and the integration of IL18BP and tumor-infiltrating CD4+ T cells could be a potential target for STAD therapy.